Dzieje rodu książąt Ostrogskich w świetle , Herbarza" Kaspra Niesieckiego - Gruntowska, Lidia (Acta Universitatis Lodziensis. Folia Historica, 2003)
The main purpose of this article was as much to look at the history of the most powerful prince family in Wołyń with the eyes of one of the greatest historians of the Saxon age - Kasper Niesiecki - as well as to find an answer to the question how much Niesiecki really knew about the history of Ostrogski family, what was an object of his interest, what matters drew his attention and what he omitted. Preparing his “Korona Polska” (“The Kingdom of Poland”) Kasper Niesiecki availed himself of the works of other heraldic historians like Bartłomiej Paprocki, Szymon Okolski or Wojciech Kojałowicz and also of the works of chronicers and historians like Jan Długosz, Maciej Miechowita, Marcin Bielski, Stanisław Orzechowski, Łukasz Górnicki and Szymon Starowolski. Moreover, he managed to gather lots of precious manuscripts, mainly monastic chronicles (especially Jesuits’). He also used thoroughly printed constitutions of the Seym, statutes, church foundation certificates, descriptions of tomb stones, occasionally printed Panegyrics and funeral speeches as well as gcneaJogical materials lent him by some noble and Magnate families. Kasper Niesiecki dedicated a major part of his work to Konstanty Ostrogski, Konstanty Wasyl Ostrogski, Anna Alojza Chodakiewicz, nee Ostrogska and to the last male descendant of the family - the founder of the estate, Janusz Ostrogski. The family of Ostrogski is shown in Niesiecki’s armorial in a very favourable light. One would be looking in vain for any criticism or any attempt to lake up difficult or controversial subjects. He paid special attention to the quantity of progeny of the described personages, to the fortune they managed to gather, the dignity and rank they gained, the battles they participated in and their relation to subject of faith. Various kinds of anecdotes take a lot of space in his story and thanks to the vivid style of the author, may give an impression of genuine report based on source materials. Undoubtedly, the historian aimed to reconstruct the family Ostrogski’s past as close to the historic truth as he could. However as his historical methodology was not perfect, he did not manage to avoid many blatant errors and mistakes, especially with reference to the first generations of the Ostróg princes. The errors also regard the dales. However, the more we approach the author’s times, the more precise and closer to reality the information are. Nevertheless it also happened then that Niesiecki was concentrated only on chosen subjects, omitting the details which could - in his opinion - cast a shadow on the past of the great princes’ family.